O estágio supervisionado da educação infantil no curso de Pedagogia da FCT/UNESP: a práxis na visão dos alunos - Oliveira, Mariana Felicio Silva de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study, linked to the Formative Processes Research Line, Childhood and Youth, is structured based on the understanding that the supervised training in Early Childhood Education should be seen as an activity that articulates theory and practice to improve initial training. Thus, the overall objective of the research was to investigate how theory and practice are addressed in curricular supervised training in Early Childhood Education, held at the Faculty of Education of the FCT / UNESP, Presidente Prudente campus - SP. The specific objectives deployed in: analyzing the Faculty of Education project to investigate the design, organization and internship structure in order to identify their role in the course; identify if it occurs on the Faculty of Education in the project investigated the intention of promoting a balance between theoretical and practical knowledge during the internship, in order to understand how it is being made, how the internships are being developed and what is the nature of the work performed and investigate how and when are promoted moments of reflection and theorization of teaching practice during the internship in the Early Childhood Education of the Faculty of Education of the FCT / UNESP. The theoretical framework assumed involved studies on: teacher training for Early Childhood Education; Faculty of Education; supervised internship and theory and practice in curricular supervised training of Early Childhood Education. This research has a qualitative approach. The participants are students in the 4th year of Education course, school year 2014, afternoon and evening periods. To obtain the data the following were performed: a documental analysis of the teaching political project course (2010-2014), a document analysis of three internship reports (nursery and pre-school); a questionnaire in 2013 to identify the profile of the graduating students and semi-structured interviews with ten students. The information obtained was transcribed, organized, coded and analyzed from the perspective of content analysis. The research findings indicate that, in the pedagogical project of the referred Education course, there is concern with the internship paperwork, the guidance as to its progress, moments of reflection and conceptualization the pedagogical work are always the responsibility of the methodology subject teacher and that there is a definite internship proposal (possibly this is done with observation and report delivery). In the internship reports analyzed, nursery and preschool, we identified that presumably was not requested a particular document structure, the records were succinct and we suppose that these documents do not have grounded critical analysis, they just provide descriptions and personal reflections, based on common sense or experience, experience of Early Childhood Education by the trainees. In the interviews with the students from the course we saw that the internships were carried out only in the form of observation and the trainee did not feel prepared for this activity. The internship guiding professor expressed concern about explaining the bureaucratic component and how to proceed in the institutions (nursery and pre-school); however, we identified the need for an internship orientation. Possibly, there was no time to reflect and theorize about its progress. The contribution of the nursery and pre-school internships were related to routine knowledge, space and observed teaching work, in other words, were associated with superficial elements, without the proper theoretical deepening. The internship model is presumably traditional and it separates theory from practice, and it must therefore relate the binomial. It is necessary to draw up an internship design that favors the theoretical and practical knowledge, with the presentation of a proposal that aims to train the future teacher for the exercise of their profession.

O presente estudo, vinculado à Linha de Pesquisa Processos Formativos, Infância e Juventude, estrutura-se a partir da compreensão de que o estágio supervisionado na Educação Infantil deve ser visto como atividade que articule a teoria e a prática para aprimorar a formação inicial. Assim, o objetivo geral da pesquisa foi investigar como a teoria e a prática são abordadas no estágio curricular supervisionado na Educação Infantil, realizado no curso de Pedagogia da FCT/UNESP, campus de Presidente Prudente - SP. Os objetivos específicos desdobraram-se em: analisar o projeto do curso de Pedagogia para investigar a concepção, a organização e a estrutura do estágio, a fim de identificar seu papel no curso; identificar se incide no projeto do curso de Pedagogia investigado a intenção de se promover a articulação entre conhecimentos teóricos e práticos no decorrer do estágio, com o intuito de compreender como ela é feita, como os estágios são desenvolvidos e qual a natureza do trabalho realizado e investigar como e quando são promovidos os momentos de reflexão e de teorização da prática pedagógica no decorrer do estágio na Educação Infantil do curso de Pedagogia da FCT/UNESP. O referencial teórico assumido envolveu estudos sobre: formação docente para a Educação Infantil; curso de Pedagogia; estágio curricular supervisionado e teoria e prática no estágio curricular supervisionado da Educação Infantil. Esta pesquisa tem uma abordagem qualitativa. Os participantes são discentes do 4º ano do curso de Pedagogia referido, ano letivo de 2014, períodos vespertino e noturno. Para a obtenção dos dados foram realizados: análise documental do projeto político pedagógico do curso (2010-2014), análise documental de três relatórios de estágio (creche e pré-escola); questionário aplicado em 2013 para identificar o perfil dos graduandos e entrevistas semiestruturadas com dez discentes. As informações obtidas foram transcritas, organizadas, codificadas e analisadas sob a perspectiva da análise de conteúdo. Os achados da pesquisa indicam que, no projeto pedagógico do curso de Pedagogia referido, há a preocupação com a parte burocrática do estágio, que a orientação quanto ao seu andamento, os momentos de reflexão e de teorização do trabalho pedagógico são sempre de responsabilidade do professor da disciplina de metodologia e que não há uma proposta de estágio definida (possivelmente este é realizado com observação e entrega de relatório). Nos relatórios de estágio analisados, creche e pré-escola, identificamos que, presumivelmente, não foi solicitada uma estrutura específica do documento, os registros eram sucintos e deduzimos que estes documentos não possuem análise crítica fundamentada, apenas apresentam descrições e reflexões pessoais, baseadas no senso comum ou na experiência, vivência da Educação Infantil pelos estagiários. Nas entrevistas com os estudantes do curso vimos que os estágios foram realizados apenas na modalidade de observação e o estagiário não se sentiu preparado para esta atividade. Os orientadores dos estágios manifestaram a preocupação de explicar a componente burocrática e como proceder nas instituições (creche e pré-escola); no entanto, identificamos a necessidade da orientação de estágio. Possivelmente, não houve momentos para refletir e teorizar sobre o seu andamento. Os contributos dos estágios da creche e pré-escola foram relacionados ao conhecimento da rotina, do espaço e do trabalho docente observado, ou seja, estiveram associados a elementos superficiais, sem o devido aprofundamento teórico. O modelo de estágio é, presumivelmente, tradicional e separa a teoria e a prática, sendo necessário, portanto, relacionar o binômio. É preciso elaborar um projeto de estágio que privilegie o conhecimento teórico-prático, com a apresentação de uma proposta que objetive formar o futuro professor para o exercício de sua profissão.
The supervised internship of early childhood education in the Faculty of Education of the FCT / UNESP: theory-practice in students' views
Keywords: Education course; Teacher training; Supervised internship; Childhood education; Theory and practice; Pedagogia; Formação de professores; Estágio supervisionado; Teoria e prática; Educação infantil